2005
DOI: 10.1159/000086754
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Progressive Supranuclear Palsy: A Clinicopathologic Study from a Population of Brain Donors

Abstract: Progressive supranuclear palsy (PSP) is the second most common parkinsonian syndrome, characterized by a ‘diverse’ clinical phenotype. Although several different diagnostic guidelines have been proposed, the early and accurate diagnosis of PSP remains problematic and neuropathology is still considered the ‘gold standard’. In order to contribute to the better clinical characterization of PSP, we conducted a postmortem study in a cohort of 22 consecutive PSP brain donors and compared our results with those of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 85 publications
(98 reference statements)
7
21
0
Order By: Relevance
“…Although our PSP-P group consists of only seven cases, due to the strict use of NINDS-SPSP criteria, the difference in survival compared with our RS cases was striking as well. The effect of higher onset-age on survival in the present study was also found in retrospective studies,20 21 35 whereas our observed predictive value of gender contrasted to a weak or absent effect on survival in several other studies,18 20 21 but not all 35. The prognostic significance of older onset-age in PSP resembles observations made in Alzheimer disease36 and Parkinson disease (PD), whereas there is conflicting evidence regarding effect on prognosis of male gender in PD 37.…”
Section: Discussionsupporting
confidence: 84%
“…Although our PSP-P group consists of only seven cases, due to the strict use of NINDS-SPSP criteria, the difference in survival compared with our RS cases was striking as well. The effect of higher onset-age on survival in the present study was also found in retrospective studies,20 21 35 whereas our observed predictive value of gender contrasted to a weak or absent effect on survival in several other studies,18 20 21 but not all 35. The prognostic significance of older onset-age in PSP resembles observations made in Alzheimer disease36 and Parkinson disease (PD), whereas there is conflicting evidence regarding effect on prognosis of male gender in PD 37.…”
Section: Discussionsupporting
confidence: 84%
“…6,16,17 Interestingly, the latency of the urogenital dysfunction is associated with the disease duration in our patients. The urogenital dysfunction might well represent frontal lobe dysfunction in PSP, given the lack of orthostatic hypotension and the absence of urogenital dysfunction before the disease onset in our study and another report.…”
Section: Discussionmentioning
confidence: 55%
“…The disorder has a prevalence of 6.4/100 000 of the population [2,3] and is the second most common syndrome in which 'parkinsonism' is a prominent symptom [4]. The first description of PSP was based on nine cases that exhibited supranuclear ophthalmoplegia, pseudobulbar palsy, dysarthria, and dystonic rigidity of the upper neck and trunk [5,6].…”
Section: Introductionmentioning
confidence: 99%